The comparison of Iranian school children performance in self-concept, self-efficacy, self-esteem and anxiety - Sahranavard, Maryam; Hassan, Siti Aishah; Elias, Habibah; Abdullah, Maria Chong (Marsland Press, 2012)
The main objective of the present study is to explore the comparison of male and female school children performance in students’ psychosocial factors; general self-concept, science self-concept, self-efficacy, science self-efficacy, self-esteem, anxiety, and science anxiety among lower secondary school children. The participants in the study consisted of 680 lower secondary school children, 14 year olds (317 male and 363 female) at Tehran and Shahriar city, the province of Tehran, Iran. Five valid and reliable instruments were used to assess Self-concept Attribute Attitude Scale, State-Trait Anxiety Inventory, Coopersmith Self-Esteem Inventory, General Self-Efficacy, and Science Self-Efficacy. Descriptive statistics, and to compare male and female students in different variables, MANOVA was used. The results showed that, except for self-concept, there is significant difference in science self-concept, self-efficacy, science self-efficacy, self-esteem, anxiety, and science anxiety between male and female students. This study supports the old finding that boys perform better than girls in the courses related to physics and this worthy performance has been reflected in their science self-concept and has resulted in larger mean score in boys in this psychological variable rather than girls.